Retrospective Analysis of Neck Masses Diagnosed by Histopathology from Chattogram General Hospital (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Neck masses are found in all age groups from many causes, ranging from congenital to acquired pathology. There is a wide variation in the presentation of neck masses concerning its site of origin, clinical presentation, and the nature of the progression of the disease. This study was performed to have an idea about the prevalence of various neck masses according to age and sex so that it would help us in diagnosing the neck masses. Materials and methods: This retrospective study was performed in the Department of Otolaryngology and Head Neck Surgery, Chattogram General Hospital, Chattogram from July 2018 and June 2019, over 97 patients presented with neck mass.  Results: Of 97 cases 69.1% were female and range from 7-77 years. The maximum case holding age group was 21- 30 years (26.8%). The histopathological diagnosis of the neck masses was inflammatory in 68 (70.1%), congenital in 5 (5.2%) and neoplastic in 24 (24.7%) cases. Chronic granulomatous lymphadenitis was the most common inflammatory lesion (50.5%) and a branchial cyst was the most common congenital mass (2.2%). Neoplastic masses were malignant in 10 (10.3%) and benign in 14 (14.4%) cases. The most common malignant neoplastic mass was a follicular carcinoma (6.2%), and the most common benign neoplastic mass was goitre (12.4%).  Conclusions: Cervical lymphadenopathy was the most commonly encountered neck mass. Most of the neck masses are benign. Out of these cervical lymph nodes, tubercular lymphadenopathy was most common.JCMCTA 2022 ; 33 (1) : 21-24